A xanthene derivative, free or associated to nanoparticles, as a new potential agent for anticancer photodynamic therapy. Issue 15 (7th July 2020) - Wang, Kaiming; Zhang, Juan; de Sousa Júnior, Wellington Tavares; da Silva, Victor Carlos Mello; Rodrigues, Mosar Correa; Morais, José Athayde Vasconcelos; Jiang, Chengshi; Longo, João Paulo Figueiró; Azevedo, Ricardo Bentes; Muehlmann, Luís Alexandre
Abstract: The efficacy and safety of photodynamic therapy (PDT) have drawn much attention from clinicians and researchers in the field of anticancer treatments since the last century. Despite the numerous positive outcomes, the works on PDT have brought to light over the last decades, much room remains for improvements in PDT tools, mainly on the photosensitizer molecules. This work reports the first experiments evidencing the photosensitizing activity of DHX-1, a xanthene derivative-based near-infrared probe recently described in the literature, both as a free molecule and associated to a nanostructured lipid carrier. The results show that the DHX-1 presents a broad band of light absorption within the optical window of biological tissues (600–800 nm), generates reactive oxygen species when photoactivated, and is phototoxic against murine breast adenocarcinoma 4T1 cells and murine fibroblast NIH-3T3 in vitro . Moreover, the association of DHX-1 to a nanostructured lipid carrier strongly reduced its phototoxicity against the normal cell line.